Implications of Knowledge-Based Management on Service Quality Management - Popșa, Roxana Elena (International Journal of Economic Practices and Theories, 2014)
Modern management creates opportunities for quality management in organizations providing services in the current economic environment characterized by the revolution of knowledge and technological progress. The transition from the industrial age to knowledge-based period indicates that the source of competitive advantage is today the acquisition of knowledge inside and outside the organization, a prerequisite for achieving excellence and performance. The trend of knowledge-based management of organizations can be observed in most areas of activity. Thus, contemporary business is going through a process of adaptation to the new management concept, centered on providing quality services through continuous development of intellectual capital. However, new technologies offer the management of organizations providing services the ability to adapt to ever-changing customer demands and preferences. In this context, this research topic is based on an extensive study of applied and fundamental research works in order to determine how knowledge-based management influences value creation and competitive advantage by service providers.